PERFORMANCE OF VEGETABLE CROPPING AND EFFECTS ON SOIL PROPERTIES UNDER CONSERVATION AGRICULTURE MANAGEMENT IN SOUTHEASTEARN BRAZIL - Branco, Roberto Botelho Ferraz; Silveira, Jane Maria de Carvalho; Maia, Douglas Florian; Carvalho, Fernando de; Lima, JÃºlia Carvalho Gomes de; Figueiredo, GetÃºlio Coutinho (REVISTA DE AGRICULTURA, 2022)
Conservation Agriculture (CA) is based in principles of the minimum soil disturbance, preservation of organic mulch on soil surface and crop rotation. Therefore, this study aimed to compare the CA versus conventional tillage for tomato and broccoli cropping. The experimental treatments were two tillage method (no-tillage and conventional tillage) as the main plot and species of cover crops, legumes, grasses and a mix (legume + grass) as subplot. Soil properties and vegetable agronomic performance were assessment. No-tillage provided higher soil water content and increased soil fertility and higher soil mechanical resistance to penetration than conventional tillage. Broccoli growth and yield were impaired under no-tillage, while tomato had greater root length and similar yield compared to the conventional tillage. Regarding to the cover crops there was no difference on the experimental traits. Conservation Agriculture is recommended to increase soil fertility and soil water storage as well as for ensure sustainable vegetable production.Â Â